Integrating Parasitological and Entomological Observations to Understand Malaria Transmission in Riverine Villages in the Peruvian Amazon - Rosas-Aguirre, Angel (2021)
This work was supported by the Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica (grant number 008-2014-FONDECYT); the Academie de Recherche et d'Enseignement Superieur-Commission de la Cooperation au Developpement of Belgium (grant number ARES-CCD, PRD-Peru 2014-2019 to N. S., A. L. C., and A. R. A.); World Health Organization Special Programme for Research and Training in Tropical Diseases (grant number 201460655 to D. G.); and National Institutes of Health, National Institute of Allergy and Infectious Diseases (grant numbers U19AI089681 to J. M. V. and R01AI110112 to J. E. C.). A. R. A. is a Postdoctoral Researcher of the Fonds de la Recherche Scientifique (FNRS, Belgium).